2003
DOI: 10.1139/g03-081
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic analysis of the 61D-61F region of the third chromosome ofDrosophila melanogaster

Abstract: Assigning functional significance to completed genome sequences is one of the next challenges in biological science. Conventional genetic tools such as deficiency chromosomes help assign essential complementation groups to their corresponding genes. We describe an F2 genetic screen to identify lethal mutations within cytogenetic region 61D-61F of the third chromosome of Drosophila melanogaster. One hundred sixteen mutations were identified by their failure to complement both Df(3L)bab-PG and Df(3L)3C7. These a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Rat and mouse Sac1 proteins are ubiquitously expressed in adult and embryonic tissues, with highest expression in Purkinje cells, have 35% sequence identity with yeast Sac1 and are also enriched at ER and Golgi membranes . Drosophila Sac1 is expressed in all tissues and stages of development, shows 47% identity with mammalian Sac1, and associates with ER and Golgi membranes . Human Sac1 shares 32% and 95% identity with yeast and rat Sac1, respectively, and is also present at ER and Golgi membranes .…”
Section: Sac1 Protein Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Rat and mouse Sac1 proteins are ubiquitously expressed in adult and embryonic tissues, with highest expression in Purkinje cells, have 35% sequence identity with yeast Sac1 and are also enriched at ER and Golgi membranes . Drosophila Sac1 is expressed in all tissues and stages of development, shows 47% identity with mammalian Sac1, and associates with ER and Golgi membranes . Human Sac1 shares 32% and 95% identity with yeast and rat Sac1, respectively, and is also present at ER and Golgi membranes .…”
Section: Sac1 Protein Characterizationmentioning
confidence: 99%
“…The first mutations in Drosophila sac1 were isolated in a screen for essential genes in the 61D‐61F region of chromosome III . sac1 null mutant flies die as embryos due to defects in DC .…”
Section: Sac1 Function In Drosophila Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that Sac1 is required for normal eye development in Drosophila (Wei et al, 2003b). Sac1 is essential for viability in Drosophila (Wei et al, 2003a,b).…”
Section: Introductionmentioning
confidence: 99%